Free vibration of fluid filled shells using ANSYS finite element analysis - Khor, Bryan Ming Hui (Nanyang Technological University, 2021)
Pressure vessels are widely used as containment units in the petrochemical, pharmaceutical and oil and gas industries. They are sometimes required to withstand large amounts of internal pressure and vibration during operating conditions. This project aims to model cylindrical pressure vessels and investigate the effects of contained fluid on the vibrational frequencies and mode shapes of pressure vessels. The project uses ANSYS Mechanical APDL to conduct Finite Element Analysis on cylindrical shells with a range of shell thickness values. The fluid level in the shell is varied and the effect of the fluid level on the natural frequencies and mode shapes is studied. The analysis in this project shows that as the fluid level increases the natural frequencies generally decrease and the corresponding mode shape also changes.